2021
DOI: 10.3390/microorganisms9112186
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Grasses and Epichloë Endophytes and Its Significance to Biotic and Abiotic Stress Tolerance and the Rhizosphere

Abstract: Cool-season grasses are the most common forage types in livestock operations and amenities. Several of the cool-season grasses establish mutualistic associations with an endophytic fungus of the Epichloë genus. The grasses and endophytic fungi have evolved over a long period of time to form host-fungus specific relationships that confer protection for the grass against various stressors in exchange for housing and nutrients to the fungus. This review provides an overview of the mechanisms by which Epichloë end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 205 publications
(261 reference statements)
0
14
0
Order By: Relevance
“…Epichloë endophytes colonize the aboveground tissues of grasses but not the roots. Associations are generally symptomless, and transmission in many associations is entirely vertical in nature, through the seed of host plants [ 9 ]. The presence of an Epichloë sp.…”
Section: Introductionmentioning
confidence: 99%
“…Epichloë endophytes colonize the aboveground tissues of grasses but not the roots. Associations are generally symptomless, and transmission in many associations is entirely vertical in nature, through the seed of host plants [ 9 ]. The presence of an Epichloë sp.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that the presence of an Epichloeendophyte promoted plant growth, biotic resistance and abiotic tolerance of their host grasses (Bastias et al ., 2017;Xia et al ., 2018b;Hewitt et al ., 2021;Lee et al ., 2021). Studies have provided an understanding of how symbiotic microbes improved drought tolerance through different strategies (Swarthout et al ., 2009;de vries et al ., 2020;Decunta et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…root arbuscular mycorrhizal fungi and foliar Epichloë endophytes) enhanced plant drought tolerance through many strategies, such as absorbing water/nutrient through external hyphae of mycorrhizal and ectomycorrhizal fungi under drought conditions (de vries et al ., 2020;Hewitt et al ., 2021). About 20-30% of grass species in the family Poaceae may be symbiotic with a foliar Epichloë fungal endophyte, promoting plant growth and enhancing persistence (Schardl et al ., 2004;Gibert et al ., 2019;Lee et al ., 2021). Epichloë endophytes colonize the aboveground tissues of grasses but not the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical transmission implies a lack of genetic recombination and diversity. The fungus host-specific consociation that improves plant performance is also independent to biotic or abiotic conditions ( Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%